Evaluación de Características Fisiológicas de maíz (Zea mays) de cinco colectas (Línea UTC) en el Centro Experimental Salache CEASA- 2022. - García Bosmediano, Erika Estefanía (2022)
One of the main problems that affect the quality of the seed of agricultural cultures is its correct harvest and post-harvest, conservation, and maintenance in germplasm banks. The present research project was developed in the facilities of Granos Andinos, and the agronomy laboratory located in the CAREN faculty of the Technical University of Cotopaxi. The objective of the research work was to characterize two varieties of corn, being the UTC - 003 chulpi corn; UTC – 044 corn the study objects, the same ones that were collected in five different years, the evaluated lines were: UTC – 003 chulpi corn, collections 2015 and 2020; UTC line – 044 corn, collected in the years 2018, 2019 and 2020. These collections were subjected to the application of a series of physiological tests described by (Krzyzanowski et al., 1999), (FAO and AfrizaSeeds, 2019), and (RAS, 2009), which refer to the standards of the International Seed Analysis Association (ISTA) and which allowed evaluating seed moisture, standard germination, tetrazolium, electrical conductivity, accelerated aging, cold test, rate of emergence rate. A completely randomized design with five treatments and four replications was used. With the usage of the characterization tests, it was possible to efficiently detect the quality levels of the corn seed collections studied. This fact allows us to conclude that the tests used revealed that the physiological quality levels of corn seeds of the UTC-044 line of the 2020 collection still show germination vigor in the current year, while negative data of a null level of vigor and viability in the tests showed the UTC-044 lines of the 2018 and 2019 collections, and the UTC-003 line of the 2015 and 2020 collections. All the mentioned tests have a number of advantages; rapid determination of vigor and viability of seed lots, and an adequate evaluation of germination capacity.